Pengaruh Fitur Paylater Terhadap Pembelian Kompulsif Pengguna Shopee Di Kota Bogor - Sabas Setyohadi, J; Tjitrosumarto, Sumaryati; Prasetyono, Hendro (CV. Multi Kreasi Media, 2023)
This research aims to determine the effect of the paylater feature on the compulsive buying of Shopee users in Bogor City. The design used in this research is a quantitative method, called a quantitative method because the research data is in the form of numbers and the analysis uses statistics. The sample obtained was 100 Shopee users using a nonprobability sampling technique. The data collection technique uses a questionnaire. The results of this research, (1) Simple linear regression analysis obtained the regression equation Y = 4.3442 + 0.7684, (3) The coefficient of determination is 30.36% and the remaining 69.64% is influenced by other factors not included in the research, (4) It is known that there is a significant influence of the paylater feature on the compulsive buying of Shopee users in Bogor City, because the t value is equal to 6.1833 and ttable 1.661 then Ho is rejected and Ha is accepted.